2021
DOI: 10.3389/fnut.2021.672390
|View full text |Cite
|
Sign up to set email alerts
|

A Microbiome-Driven Approach to Combating Depression During the COVID-19 Pandemic

Abstract: The significant stressors brought about and exacerbated by COVID-19 are associated with startling surges in mental health illnesses, specifically those related to depressive disorders. Given the huge impact of depression on society, and an incomplete understanding of impactful therapeutics, we have examined the current literature surrounding the microbiome and gut-brain axis to advance a potential complementary approach to address depression and depressive disorders that have increased during the COVID-19 pand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 237 publications
0
8
0
Order By: Relevance
“…An interesting issue recently raised by scientists is the impact of probiotics on mood improvement during COVID-19. Probiotics, in addition to restoring intestinal balance, reduces risk of colonization of the intestine by opportunistic pathogens [ 58 ]. According to Rogers et al [ 59 ], COVID-19 infection could result in posttraumatic stress disorder (PTSD).…”
Section: Factors Affecting Gut Microbiotamentioning
confidence: 99%
“…An interesting issue recently raised by scientists is the impact of probiotics on mood improvement during COVID-19. Probiotics, in addition to restoring intestinal balance, reduces risk of colonization of the intestine by opportunistic pathogens [ 58 ]. According to Rogers et al [ 59 ], COVID-19 infection could result in posttraumatic stress disorder (PTSD).…”
Section: Factors Affecting Gut Microbiotamentioning
confidence: 99%
“…The association between intestinal microbiota and mood disorders is currently a hot research topic. Numerous studies have shown that depression and anxiety are associated with an imbalance of intestinal flora, which leads to abnormality in the gut-brain axis [71,72]. Ghannoum et al reported that altered intestinal flora in the multiple dimensions of the gut-brain axis had a negative impact, including excessive activation of the HPA axis (cortisol), neural circuits, and the level of neurotransmitters such as dopamine and serotonin, as well as excessive production of pro-inflammatory cytokines in the immune system (e.g., IL-6) and the destruction of the intestinal barrier [71].…”
Section: Intestinal Microbiological Mechanismmentioning
confidence: 99%
“…The association between intestinal microbiota and mood disorders is currently a hot research topic. Numerous studies have shown that depression and anxiety are associated with an imbalance of intestinal flora, which leads to abnormality in the gut-brain axis [ 71 , 72 ]. Ghannoum et al .…”
Section: Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The probiotics could be useful when ingested in a definite quantity through the interaction with commensal gut bacteria and their benefits are mediated by several mechanisms referred to the hypothalamic-pituitary-adrenal (i.e., HPA) axis, the immune response and inflammation, and the production of neurohormones and neurotransmitters [ 76 ]. The rebalancing of a dysbiotic flora through the use of psychobiotics represents a therapeutic goal as a complementary intervention to standard care, especially for depressive symptoms [ 77 , 78 ], even if additional RCTs in clinical populations are warranted to better evaluate their efficacy. Further, the stimulation of the vagus nerve is also recognized as an effective neurophysiological treatment in depression [ 79 ] because of the possibility to alter the cerebrospinal fluid concentration of neurotransmitter or their metabolites (e.g., GABA, and 5h1AA), and influence the functionality of certain brain regions that are dysregulated in mood disorders (i.e., orbitofrontal cortex, insula, thalamus and hypothalamus, and cingulate and hippocampus) [ 80 ].…”
Section: Conclusion and Implications For Clinical Neuroscience Resear...mentioning
confidence: 99%